Implementation of Diet Consultant Management System - Ankita Sardar; Kirtee Rathod; Natasha Bagde; Payal Balvir (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The Diet Consultation Management System (DCMS) represents a pivotal innovation in the realm of dietary counselling and nutrition management. In today’s fast-paced society, where lifestyle factors and dietary habits play a significant role in shaping health outcomes, the demand for personalized, accessible, and evidence-based dietary guidance has never been more pronounced. This paper provides an overview of the DCMS, highlighting its key features, functionalities, and potential impact on improving dietary behaviours and also health results. The DCMS is a digital platform designed to streamline the delivery of dietary consultation services, applying cutting-edge technology like machine learning (ML) and artificial intelligence (AI), and mobile computing. By harnessing the power of these technologies, the DCMS offers tailored dietary recommendations and meal plans based on individual preferences, health goals, and nutritional requirements. Through interactive interfaces and user-friendly applications, individuals can access personalized dietary guidance anytime, anywhere, empowering them to make informed decisions about their nutrition and lifestyle.